Response of several coniferous shrubs to the application of herbicide containing foramsulfuron and methylsodium iodosulfuron - Pacholczak, Andrzej; Nowakowska, Karolina; Gromadzka, Dorota (Polish Journal of Agronomy, 2022)
The chemical method is the most popular method of weed control due to its efficiency and low costs. A broad assort- ment of herbicides allows to choose right preparations to control weeds in field production of ornamental shrubs. An experiment on the use of the foramsulfuron- and methylsodium iodosulfuron- -containing herbicide was carried out in 2015. coniferous plants: Picea pungens f. glauca, Pinus mugo subsp. mugo and Thuja oc- cidentalis ‘Smaragd’ were planted in the field and their height was measured. When the growth ceased the plants were measu- red again (in mid-September) and plant material for biochemical analyses was then sampled. The results show that spraying plants with the herbicide in the dosage of 0.15 kg .ha-1 , in April, befo- re growth started, was not toxic for the conifers Picea pungens f. glauca and Pinus mugo subsp. mugo while Thuja occidenta- lis ‘Smaragd’ proved sensitive to the treatment. The preparation applied together with the recommended adjuvant efficiently con- trolled most of the weeds. The weeds resistant to the herbicide were: Convolvulus arvensis, Equisetum arvense and Cerastium holosteoides. In two insensitive taxa the foliar application of the herbicide resulted in an increase in total soluble sugars, free ami- no acids and polyphenolic acids as well as in an increased peroxi- dase activity in plant shoots while the content of chlorophyll and catalase activity were decreased. In the sensitive Thuja occiden- talis ‘Smaragd’ the content of free amino acids and polyphenolic acids as well as activities of peroxidase and catalase increased while the levels of chlorophyll, total soluble sugars and hydrogen peroxide fell.